Penerapan Komunikasi Terapeutik Pada Pasien Skizofrenia Dalam Mengontrol Halusinasi Di RS Jiwa Menur Surabaya: Application of Therapeutic Communication in Schizophrenia Patients to Control Hallucinations at Menur Mental Hospital, Surabaya - Yosi Apriliani; Esti Widiani (Fakultas Keperawatan Universitas Andalas, 2020)
Hallucinations are absorption (perception) of the five senses without any stimulation from outside. The way to control hallucinations was by conducting therapeutic communication. Therapeutic communication is communication done by nurses during nursing interventions to help the patient's healing process and help patients overcome their problems through communication. Nurse's therapeutic communication has four phases of communication namely pre-interaction, orientation or introduction, work and termination. This study aims to improve the ability of people with schizophrenia in controlling hallucinations in Menur Mental Hospital Surabaya. The method in this research was a case study using two subjects. The results of this study indicate that after doing therapeutic communication with a frequency of 6 sessions in 6 days both subjects experienced an increase in the ability to control hallucinations. Therapeutic communication can improve the ability to control the hallucinations of the subject if it is done according to the stages.